Strategi Pengembangan Sub Terminal Agribisnis (STA) Salak Pondoh di Kabupaten Sleman - Agus Dwi Nugroho; Lestari Rahayu Waluyati; Fatkhiyah Rohmah; Ali Hasyim Al Rosyid (Universitas Muhammadiyah Yogyakarta, 2017)
The purpose of this study is to know the existing conditions and to identify need of assesements for Sub Terminal Agribisnis (STA) Tempel in Sleman Regency. Data were collected through direct observation, focus group discussion (FGD) and study documents from related institutions. The existing conditions of STA Tempel was analyzed qualitatively and quantitatively, while need of assessment for STA Tempel was analyzed by SWOT. The results showed that STA Tempel has not been able to perform the function properly. To improve the performance, STA Tempel must increase function of marketing of agricultural commodities; integrate with other trading activities; develop promotion; optimize of human resource functions; build modern facilities and infrastructures; and optimize the role of STA as a training and education center.